EFFECT OF TANGIBILITY ON CUSTOMER SATISFACTION AMONG MICRO FINANCE BANKS CUSTOMERS IN KENYA - Nyabundi, Hakim; Aliata, Victor; Odondo, Alphonce (European Journal of Business and Strategic Management, 2021)
Purpose: Financial markets and institutions are central to the process of economic growth. The provision of credit has increasingly been regarded as an important tool for raising the incomes of populations, mainly by mobilizing resources to more productive uses. However, microfinance institutions in Kisumu City Kenya are still far off from reaching the required customer satisfaction index. The main purpose of the study was to establish the effect of tangibility on customer satisfaction among micro finance banks (MFB) customers in Kisumu City. Methodology: This study was anchored on a Market based theory; Survival based theory and the Expectancy Disconfirmation theory. A correlation research design was used. Study targeted 10,300 MFB customers in Kisumu City. A sample size of 370 MFB customers was drawn from the target population using simple random sampling technique. The study used primary data from questionnaires. Findings: The findings indicated that Tangibility is associated with 63.1% of the variation in customer satisfaction, an increase in tangibility affects customer satisfaction by 0.341. The correlation analysis to determine the effect of tangibility on customer satisfaction shows a significant correlation existed (r = 0.631, p < 0.05). This shows 63.1% of the variations on customer satisfaction are associated with tangibles. Unique Contribution to Theory, Practice and Policy: The organization needs to train employees on various aspects of tangibility. Systems should be in place that ensures certain aspects like security and quality are retained and improved throughout customers' lifetime.